Pengaruh pemberian jenis pakan yang berbeda terhadap pertumbuhan benih ikan Betok (Anabas testudineus Bloch) - Rustiana Widaryati (Fakultas Peternakan Universitas Kristen Palangka Raya, 2016)
This study aims to find out what kind of feed is best for the growth of the climbing perch (Anabas testudineus) and the level of efficiency of the feeds. This study used a completely randomized design (CRD) consisting of 3 treatment, Treatment A (feed with earthworms), treatment B (feed with waste rice), treatment C (feed with duckweed). The parameters observed were absolute weight growth, feed conversion, survival rate (SR) and water quality. Results of this study showed that different feed types were highly significant effect (P